2019
DOI: 10.1038/s41467-018-07963-8
|View full text |Cite|
|
Sign up to set email alerts
|

Online photochemical derivatization enables comprehensive mass spectrometric analysis of unsaturated phospholipid isomers

Abstract: Mass spectrometry-based lipidomics is the primary tool for the structural analysis of lipids but the effective localization of carbon–carbon double bonds (C=C) in unsaturated lipids to distinguish C=C location isomers remains challenging. Here, we develop a large-scale lipid analysis platform by coupling online C=C derivatization through the Paternò-Büchi reaction with liquid chromatography-tandem mass spectrometry. This provides rich information on lipid C=C location isomers, revealing C=C locations for more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
209
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(219 citation statements)
references
References 45 publications
6
209
1
3
Order By: Relevance
“…An extremely useful feature offered by lipid isomer analysis, is the relative quantitation achieved at high precisions without requiring the use of lipid standards, which is not readily available 25,26 . Remarkably, our recent study demonstrated close correlation between the lipid C=C location isomer compositions and Type II diabetes 30 , which owes to a tighter regulation on lipid desaturation, allowing efficient elimination of interferences due to variations among samples.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…An extremely useful feature offered by lipid isomer analysis, is the relative quantitation achieved at high precisions without requiring the use of lipid standards, which is not readily available 25,26 . Remarkably, our recent study demonstrated close correlation between the lipid C=C location isomer compositions and Type II diabetes 30 , which owes to a tighter regulation on lipid desaturation, allowing efficient elimination of interferences due to variations among samples.…”
mentioning
confidence: 64%
“…Comprehensive structural elucidation of lipids by PB-MS 3 . The use of photochemistry and tandem MS for lipid structure analysis have been systematically studied on both nano-electrospray ionization (nanoESI)-MS 25,34 and LC-MS platforms 30 . All these studies used acetone as the reactant owing to its miscibility with water and other commonly used organic solvents, high reaction kinetics and compatibility with electrospray ionization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include electron impact excitation of ions from organics (EIEIO), 23 ozone-induced dissociation (OzID), [24][25][26] and ultraviolet photodissociation (UVPD). 27,28 All these developments greatly expand the toolbox for lipid analysis; more importantly, they not only provide rst-time analysis of lipidomes at the isomer level 11,19,[28][29][30] but also demonstrate the link between altered isomer compositions with disease quantitatively and spatially. [31][32][33][34] Radical-directed fragmentation has attracted increasing attention in MS/MS method development due to its unique capabilities in differentiating structural isomers of biomolecules, which otherwise cannot be obtained from chargedirected fragmentations typically seen from CID.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xia group developed a large-scale lipid analysis platform by coupling online C=C derivatization through the P-B reaction with LC-MS/MS to distinguish C=C location isomers. They revealed C=C locations for more than 200 unsaturated glycerophospholipids in bovine liver among which 55 groups of C=C location isomers were identified [44]. Compared with the chemical derivatization methods of carbon-carbon double bond previously reported, P-B derivatization reaction has several unique advantages, including fast reaction kinetics suitable for online coupling with ionization, wide applicability to different lipid classes, simplicity of implementation, and compatibility with commercial MS instruments with lower energy collision-induced dissociation capability.…”
Section: Carbon-carbon Double Bond-based Derivatization Approach Of Umentioning
confidence: 99%